Magyar NB-l-es lagdarúgó-mérkőzések nézőinek társadalmi összetétele és motivációi (Szociológiai Szemle, 2024)
This study is based on a survey carried out in the 1992/1993 soccer season in the stadia of all Hungarian first league teams with the aim of collecting information about the major social and demographic characteristies of fans attending the matches, about their motivations and match-day routin. Taking into consideration the special methodological problems the sample was selected gradually and randomly (N=2608), the data were collected by personal interviews, indepth interviews and by document analysis. The findings provide the readers not only with wide-range facte concerning the age, sex, level of education and profession of spectators in the stands and on the grounds as well as concerning their sport-related values and motivations, but with thourough analysis of the main social, economic and cultural factors influencing the social composition and behaviour of the Hungarian soccer crowd. In conclusion the author points out some dysfunctional consequences of first league soccer matches in Hungary causing more detriment than benifit both at individual and social levels.